Adult Degenerative Scoliosis. Issue 3 (April 2016) - Graham, Randall B.; Sugrue, Patrick A.; Koski, Tyler R.
Abstract : The treatment of adult degenerative scoliosis begins in the outpatient setting when evaluating a patient both radiographically. Assessing the flexibility of the deformity is essential in determining what techniques will be required to achieve the goals of correction. Ultimately the surgeon's comfort and experience and the patient's medical risk stratification determine the strategy needed to address either a focal pathology or ultimate deformity correction.